Heavy Metal Content of Total Suspended Air Particles in the Heavily Industrialized Town of Gebze, Turkey - Ergenekon, Pınar; Ulutas, Kadir (Springer, 2014)
Air pollution is a serious environmental problem in industrialized towns, where a significant portion of the residents live in close proximity to factories and major highways with high traffic load. In this study, the ambient air quality in Gebze, an industrial region with an area of 438 km(2) and a population of 300,000, was characterized in terms for total suspended particulate matter and its composition of trace elements, i.e. Cd, Cr, Cu, Fe, Mn, Ni and Pb. Samples were collected using high volume samplers from March to June 2009 at two sites during the day and the night. A significantly higher Cu concentrations during night suggested that Cu emissions were the result of a local source. The known air toxics, Cd and Ni, had average concentrations (34 and 43 ng/m(3), respectively) higher than proposed by the European Union's ambient air quality standards. These results highlight the potential health risks for the local population.
Keywords: Air quality; Source apportionment; Trace elements; Total suspended particles; Urban aerosol